THE DEVELOPMENT OF CONTEXTUAL-BASED TEXTBOOK ON CONSTITUTIONAL THEORY AND LAW COURSE IN PANCASILA AND CIVIC EDUCATION STUDY PROGRAM OF TEACHER TRAINING AND EDUCATION FACULTY OF SRIWIJAYA UNIVERSITY - Kurnisar, Kurnisar; Dianti, Puspa; Camellia, Camellia (Sriwijaya University Learning and Education International Conference, 2018)
Pancasila and Civic Education Study Program of Teacher Training and Education Faculty of Sriwijaya University is one of the social science study programs which courses contain many theories or concepts. One of them is constitutional theory and law course. In conveying the material, a lecturer as the advisor should prepare a textbook containing content which is able to facilitate the students to understand the material so that the learning becomes more meaningful. Therefore, the researcher, as the advisor of constitutional theory and law course, compiled a contextual-based textbook. This research was aimed to produce textbook of constitutional theory and law course based on context to improve students’ understanding. This research was a type of research and development referring to R & D Cycle Borg and Gall and was aligned with the established research objectives. The steps in this research were conducting a preliminary study to find out things that students need during the learning as well as developing and testing the product of constitutional theory and law textbook. Furthermore, the techniques for collecting the data were documentation, questionnaires, and interviews. The result of this research showed that the development of contextual-based textbook is able to improve the understanding of the material in constitutional theory and law course.